2021
DOI: 10.1155/2021/6665586
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Helminth Infections and Associated Risk Factors among School-Aged Children of Bamendjou Community, West Region of Cameroon

Abstract: Background. Infection with intestinal nematodes is of major public health concern worldwide, and school-age children and pregnant women are the principal victims. The present study was undertaken to provide baseline information on the status of gastrointestinal nematodes among school-age children in Bamendjou. Material and Methods. Four hundred and ninety-three (493) stool samples were collected from school children in six (6) different schools (two nursery, two primary, and two secondary schools). Qualitative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
4
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 14 publications
4
4
2
Order By: Relevance
“…The prevalence rate of double parasitism was 2.72 percent, which is nearly similar to the prevalence rates reported by Ragunathan et al [ 35 ], Ruth et al [ 36 ], and Hailu and Ayele [ 37 ], which were 1.8 percent, 1.2 percent, and 0.9 percent, respectively. In contrast, our prevalence rate did not coincide with those of certain previous Ethiopian research which reported a greater prevalence rate [ 25 , 31 ].…”
Section: Discussionsupporting
confidence: 86%
“…The prevalence rate of double parasitism was 2.72 percent, which is nearly similar to the prevalence rates reported by Ragunathan et al [ 35 ], Ruth et al [ 36 ], and Hailu and Ayele [ 37 ], which were 1.8 percent, 1.2 percent, and 0.9 percent, respectively. In contrast, our prevalence rate did not coincide with those of certain previous Ethiopian research which reported a greater prevalence rate [ 25 , 31 ].…”
Section: Discussionsupporting
confidence: 86%
“…Njitchouang et al, (2021) found that campaigns or education alone cannot control these infectious if the environment is not properly managed, leading to continual helminth infections and outbreaks (Anegagrie et al, 2021). Moreover, the study of Ruth et al, (2021) was in accordance with Getaneh, (2021), who found that never wearing shoes was a factor that promoted infection when contacting the soil (Anegagrie et al, 2021 andRuth et al, 2021).…”
Section: Five Statisticallysupporting
confidence: 76%
“…In addition, shoe-wearing was reported to be at a low level (Silvia et al, 2021) noted that not wearing shoes when performing farming tasks or going outside can lead to infection (Rahmi et al, 2021 andSuntaravitun andDokmaikaw, 2018). Although these were in contrast with a study by Ruth et al, (2021) who found that the rate of infection with soil-borne parasites was higher in females than males (Ruth et al, 2021 andTegen andDamtie, 2021) found the males and females had no difference in infection rates (Tegen and Damtie, 2021), researcher resists the previous logic.…”
Section: Sub-gained Issue For Suggestion Synthesismentioning
confidence: 95%
“…The use of footwear, a hygiene behavioral component is connected with the frequency of helminth infection in the study done in Bamendjou Community, Upper Plateaux Division, Western Cameroon (p = 0.04) (40). Similar research in Tuah Negeri, one of the subdistricts from Musi Rawas Regency including the province of South Sumatra, Indonesia mentions the incidence of helminth infection was found in primary school children who use less footwear (p = 0,000) (30).…”
Section: Footwear Use and Play On The Groundmentioning
confidence: 59%